Distribution of isopod parasites in commercially important marine fishes of the Miri coast, East Malaysia - Anand Kumar, A.; Rameshkumar, G.; Ravichandran, S.; Ramasamy, Nagarajan; Prabakaran, K.; Ramesh, M. (2016)
Isopods occur very commonly as parasites in food fishes. Parasitic isopods are typically marine and usually inhabit the warmer seas. They are blood-feeding; several species settle in the buccal cavity of fish, others live in the gill chamber or on the body surface including the fins. Isopods can cause morbidity and mortality in captive fish populations. The infestation usually pressure atrophy often accompanies the presence of larger parasites. The present study was aimed at collecting information on the neglected group of isopod parasites of the marine fishes from the Miri coastal environment, East Malaysia. A very little information available regarding the distribution of isopod parasites of Malaysian coastal environment. In the present study, nine isopod parasites were oberved from ten marine fish species. The maximum number of parasites were observed in the months of June and October, 2013. Maximum prevalence was observed in October (50 %) and the minimum was observed in June (7.14 %). The parasitic infestation may lead to an economic loss in commercial fish species.